Prognostic significance of the CRP/Alb and neutrophil to lymphocyte ratios in hepatocellular carcinoma patients undergoing TACE and RFA. Issue 9 (16th August 2019) - Shen, Yanjun; Wang, Huige; Li, Wendong; Chen, Jinglong
Abstract: Background: The C‐reactive protein (CRP)/albumin (Alb) ratio (CAR) is a basic inflammatory factor that has been related to poor survival of patients with various tumors. Our research retrospectively examined the relationship between the CAR and the prognosis of hepatocellular carcinoma (HCC). Methods: This study included 172 patients with HCC who were treated with transcatheter arterial chemoembolization (TACE) and radiofrequency ablation (RFA). Results: The CAR was weakly related to the neutrophil/lymphocyte ratio (NLR, r  = .159, P  = .037) and the lymphocyte/monocyte ratio (LMR, r  = −.263, P  = .001). The Glasgow Prognostic Score (GPS) (0/1‐2) was related to liver cirrhosis ( P  = .003), tumor number ( P  = .02), Child‐Pugh grade ( P  = .001), the platelet/lymphocyte ratio (PLR, P  = .006), and the LMR ( P  = .021). Correlation analysis demonstrated that an elevated CAR was markedly correlated with the tumor size ( P  = .019), alpha‐fetoprotein (AFP) level ( P  = .033), thrombosis of the portal vein ( P  = .004), the NLR ( P  = .036), and the LMR ( P  = .001). Multivariate analysis indicated that the prognosis of the CAR‐High and NLR‐High cohort (mOS = 7 months) was significantly worse than those of the CAR‐High or NLR‐High cohort (mOS = 15 months) and the CAR‐Low and NLR‐Low cohort (mOS = 26.5 months). Conclusions: Combination of the NLR and the CAR represents a convenient, quick, and noninvasive biological marker that could improve prognostic prediction in patients with HCC.